2001
DOI: 10.1042/cs20010039
|View full text |Cite
|
Sign up to set email alerts
|

Increase in circulating levels of cardiac natriuretic peptides after hormone replacement therapy in postmenopausal women

Abstract: The mechanisms that mediate the cardioprotective action of steroid hormones in postmenopausal women are poorly understood. To study the inter-relationship between female steroid hormones and cardiac natriuretic peptides, plasma levels of atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) were measured in postmenopausal women, both before and after oestrogen replacement therapy. A total of 22 healthy postmenopausal women (mean age 51.9+/-4.6 years) were enrolled in the study; all had been post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 21 publications
0
45
1
Order By: Relevance
“…For example, androgens, which promote the development of lean mass, may suppress natriuretic peptide release, 17,18 whereas estrogens, which are associated with lower lean mass, increase natriuretic peptide levels. 19 Less likely hypotheses to explain our observations include the possibility that lean mass secretes a substance that leads to BNP and NT-proBNP degradation, or that lean mass contributes directly to BNP and NT-proBNP clearance. Further studies will be needed to confirm these findings and to explore the associated mechanisms.…”
Section: Discussionmentioning
confidence: 91%
“…For example, androgens, which promote the development of lean mass, may suppress natriuretic peptide release, 17,18 whereas estrogens, which are associated with lower lean mass, increase natriuretic peptide levels. 19 Less likely hypotheses to explain our observations include the possibility that lean mass secretes a substance that leads to BNP and NT-proBNP degradation, or that lean mass contributes directly to BNP and NT-proBNP clearance. Further studies will be needed to confirm these findings and to explore the associated mechanisms.…”
Section: Discussionmentioning
confidence: 91%
“…One murine-based study demonstrated that treatment with estradiol and progesterone stimulated NP gene expression in females (30 ), while another study demonstrated that testosterone suppressed volumestimulated NP release from isolated perfused rat atria (31 ). Clinically, a study of postmenopausal women demonstrated a significant increase in mean BNP concentrations after transdermal estradiol administration (32 ), while observational studies have identified inverse correlations between circulating androgens and NP concentrations (Fig. 3) (33, 34 ).…”
Section: Natriuretic Peptidesmentioning
confidence: 99%
“…Experimental studies in animals have pointed out that female sex steroids increase ANP gene expression in a dose-dependent manner and that both estradiol and progesterone are necessary to maintain suitable levels of ANP gene expression in rat cardiomyocytes (15). Furthermore, hormone replacement therapy with female steroid hormones shows a stimulatory action on the production/secretion of CNHs in postmenopausal women (46,61).…”
Section: The Cross Talk Between Cardiac Natriuretic and Sex Steroid Hmentioning
confidence: 99%